Mapping policy pathways: Urban referencing networks in public art policies - Silver, Daniel; 2024; Keidar, Noga (Urban Studies, 2024)
This article examines the dynamics of inter-referencing between cities and develops the concept of the'Urban Referencing Network' as a representation of the references made by cities to one another in policy documents. The study employs public art policies, specifically the Percent for Art policy, to investigate the structure of inter-referencing within the urban referencing network. Using a corpus of policy documents from 26 Anglophone cities with over one million residents, we analyse 150 documents containing 2178 inter-references. Combining network measurements and regressions, we explore the emergence of central nodes and the mechanisms influencing their formation. The broader field of arts and cultural policies, with its extensive inter-urban connections and professional networks, provides fertile ground for studying urban referencing networks. By integrating literature on policy mobility and urban networks, this study contributes to a deeper understanding of the circulation of urban ideas and the interplay between cities in policy-making processes. The results demonstrate that only a few cities, including New York, Chicago, London, Seattle, Los Angeles, and Montreal, emerge as central nodes, attracting the other cities' attention. Attributes of the referenced cities, like economic importance, iconicity and early adoption, determine to a great extent who are the most central nodes.
Keywords: Policy Mobility; Public Art; Urban Networks; Urban Space; Comparative Urbanism